Practical Application of Computer-Assisted Decision-Making in an Antenatal Clinic — A Feasibility Study - Anderson, G.; Llerena, C.; Davidson, D.; Taylor, T. R. (Methods of Information in Medicine, 1976)
A feasibility study is described involving the use of a computer program in an antenatal clinic whose decisions were based on the observed policies of the group of obstetricians running that clinic. In 200 test cases the programme successfully detected all »at risk« cases at the first visit. Abnormalities appearing at later visits were all detected and appropriate investigations ordered by the programme. The programme ordered rather more investigations than the obstetrician and this difference has been investigated, in some detail with reference to the full blood count, glucose tolerance test and the ultrasonogram.Since all of the basic data in the proposed clinic would be collected by the clerical staff or midwives, a comparison was made between two midwives and an obstetrician in estimating fundal height. The small number of discrepancies found was not regarded as serious from the viewpoint of the proposed clinic.This preliminary study suggests that the technique described might play a useful part in some areas of ante-natal care by relieving the obstetricians of much of the workload associated with routine cases and enabling the midwife to play a larger role in ante-natal care.
Keywords: Decision Analysis; Computer-assisted Diagnosis; Health Care; Ante-natal Care; Laboratory Tests; Nursing Personnel